Social Networks and the Externalities of Social Capital among Millennial Sheep Farmers in Bale Pulang Village, Cipada Village, Cikalong Wetan District, West Bandung - Khoiroon Nisaa; Triyanti Anugrahini (International Journal of Education, Vocational and Social Science, 2026)
This study aims to describe the social networks of millennial sheep farmers and to explain the externalities of social capital generated for the surrounding community in Kampung Bale Pulang, Cipada Village, Cikalong Wetan District, West Bandung Regency. The study employs a qualitative approach, with data collected through in-depth interviews, observation, and document analysis. The research informants include millennial farmers, community leaders, and non-farming residents. The research findings indicate that the social networks of millennial sheep farmers are formed through three dimensions of social capital, namely bonding social capital, bridging social capital, and linking social capital. Bonding social capital is reflected in regular meetings, mutual cooperation practices, and reciprocal assistance among members of the farmer groups. Bridging social capital is evident in collaborative exchanges of experience with other farmers as well as partnerships with tourism villages. Meanwhile, linking social capital is manifested through livestock training provided by Biofarma, visits from university representatives, and technical assistance from the livestock service office. The social capital that has been established generates various positive externalities for the surrounding community, including: (1) knowledge externalities, as seen in the increased knowledge of sheep farmers and the development of broader and more progressive ways of thinking; (2) externalities in reducing opportunism, reflected in increased income and the emergence of new occupational opportunities; and (3) collective action externalities, such as the use of livestock sheds as facilities for research and learning, improved access to feed and livestock resources, and the enhancement of local environmental infrastructure